LANGUAGE AND ATTITUDE - Rafika Dewi Nasution (UIN Sumatera Utara, 2017)
This article deals with Sociolinguistics, and focus on Language and Attitude, and includes about Theory of Attitude in Language, Language Attitude and Language Learning, and Application of Sociolinguistics.